La suerte de la lógica en la “Escuela de Madrid”: notas sobre una desgracia* - Vega Reñón, Luis (Revista de Filosofía, 2003)
The decisive role played by Ortega and his “School of Madrid” in modernizing the 20th century Spanish thinking is widely accepted, but their contribution to bring our logic up to day was rather unfortunate: far from backing the introduction or reception of modern logic, the “School of Madrid” attempted an alternative logic, the so-called ‘logic of vital reason’, non-viable. As it is a symptomatic failure, I’ll give a broader account of it starting from, and going through, a confrontation in this respect between the “School of Madrid” and its contemporary “School of Barcelona”.
Keywords: Modern logic; School of Madrid; School of Barcelona; Spanish reception of logic; 20th century philosophy